Pengaruh Ukuran Perusahaan, Profitabilitas Dan Umur Perusahaan Terhadap Audit Delay (Studi Kasus Pada Perusahaan Jakarta Islamic Indexs Tahun 2018-2020) - Sissah Sissah; Khairiyani; Ica Monalisa (Lembaga Pengembangan Kinerja Dosen, 2023)
Audit delay is the number of days required by the auditor to complete the audit work as measured from the closing date of the company's books, which is December 31 until the issuance of the audited financial statements. This study aims to empirically examine the effect of firm size, profitability and firm age on audit delay in the Jakarta Islamic Index companies in 2018-2020. for Sampling using purposive sampling method according to the criteria of the determination of the sample. The number of samples used in this study was 54 samples with 18 companies and 3 years of research period. This research is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. The software used for data processing is SPSS version 21. The results show the determinant coefficient has a value of 0.011 or 11%, while the rest is influenced by other variables outside the study. The results of this study indicate that partially firm size, profitability and firm age have no effect on audit delay. This study also shows that simultaneously firm size, profitability and firm age have no effect on audit delay.